2002
DOI: 10.1093/nar/30.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis: RNA recognition motif (RRM) and K homology (KH) domain RNA-binding proteins from the flowering plant Arabidopsis thaliana

Abstract: Regulation of gene expression at the post-transcriptional level is mainly achieved by proteins containing well-defined sequence motifs involved in RNA binding. The most widely spread motifs are the RNA recognition motif (RRM) and the K homology (KH) domain. In this article, we survey the complete Arabidopsis thaliana genome for proteins containing RRM and KH RNA-binding domains. The Arabidopsis genome encodes 196 RRM-containing proteins, a more complex set than found in Caenorhabditis elegans and Drosophila me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
315
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(324 citation statements)
references
References 108 publications
6
315
1
2
Order By: Relevance
“…The C. elegans genome contains ~ 100 genes encoding RNA recognition motif proteins (www.wormbase.org) [58] with unknown functions. It is possible that one or more of these genes can act redundantly with rbm-5 , which might explain why rbm-5 mutants are viable.…”
Section: Discussionmentioning
confidence: 99%
“…The C. elegans genome contains ~ 100 genes encoding RNA recognition motif proteins (www.wormbase.org) [58] with unknown functions. It is possible that one or more of these genes can act redundantly with rbm-5 , which might explain why rbm-5 mutants are viable.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the observed organization and dynamics of SR proteins in mammalian cultured cells is representative to that found in different cell types of a single organism. To address the question, we studied the organization and dynamics of member of SR splicing factors within different cell types of the flowering plant Arabidopsis thaliana.Interestingly, the Arabidopsis genome encodes 18 SR proteins, in comparison with 10 in human and two in Schizosaccharomyces pombe (Lopato et al, 2002;Lorkovic and Barta, 2002). Two SF2/ASF-like splicing factors (SR1/atSRp34 and atSRp30) and a novel family of SC35-like splicing factors (atSCL28, atSCL30, atSCL30a, SR33/atSCL33, and atSC35), as well as a family of zinc knuckle-containing SR proteins (atRSZp21, atRSZp22, and atRSZp22a) similar in their activities to human 9G8 and SRp20 have been characterized with regard to their splicing and RNA binding activities (Lazar et al, 1995; Reddy, 1998, 1999;Lopato et al, 1999a Lopato et al, ,b, 2002Lorkovic and Barta, 2002).…”
mentioning
confidence: 99%
“…Cloning of the corresponding genes showed that they resembled human nuclear (hn)RNP proteins, which form the most abundant fraction of RNA-binding proteins in the nucleus of human cells. In tobacco, five different proteins, referred to as cp28, cp29A, cp29B, cp31 and cp33, were found, while a genome-wide computer-assisted search in A. thaliana revealed eight members of this group (Lorkovic and Barta 2002), which could be classified into subgroups I-III, based on phylogenetic comparisons (Ohta et al 1995). A common feature of these polypeptides was that they contain two consensus sequence-type RNA-binding domains and an acidic N-terminal domain.…”
Section: General Rna-binding Proteinsmentioning
confidence: 99%
“…In total, 196 RRM and 26 KH domains containing proteins have been found in A. thaliana, which is more than in Drosophila melanogaster (117 domains) or in Caenorhabditis elegans (100 domains; Lorkovic and Barta 2002). However, these studies do not specify how many domains are chloroplast-localized.…”
Section: Introductionmentioning
confidence: 99%